2002
DOI: 10.1177/15648265020234s203
|View full text |Cite
|
Sign up to set email alerts
|

Ti Foyer (Hearth) Community-Based Nutrition Activities Informed by the Positive Deviance Approach in Leogane, Haiti: A Programmatic Description

Abstract: This paper details the steps to design and implement a positive deviance-informed, "Hearth" approach for the nutritional rehabilitation of malnourished children in the district of Leogane, Haiti. Groups of four to five children met daily for two weeks at the home of a local volunteer mother for nutritional and health messages and a well-balanced meal. Health messages and meal components were determined using information gathered from interviews with the mothers of positive deviant children in the community who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…In the present study, the overall mean weight gain after 120 days was statistically significant in both the PD-H and CHWNP groups. This was similar to Bolles et al's (2002) study that reported a significant increase in weight gain among children less than 5 years enrolled in PD-H in Haiti. The present study also showed more improvement in weight gain in the CHWNP group than the PD-H group.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the overall mean weight gain after 120 days was statistically significant in both the PD-H and CHWNP groups. This was similar to Bolles et al's (2002) study that reported a significant increase in weight gain among children less than 5 years enrolled in PD-H in Haiti. The present study also showed more improvement in weight gain in the CHWNP group than the PD-H group.…”
Section: Discussionsupporting
confidence: 89%
“…Nutrition programmes based on PD/Hearth models have been popularly implemented in developing settings with the advantages of cultural appropriateness, sustainable implementation and community participation (Bolles et al . ; Hendrickson et al . ; Aubela et al .…”
Section: Discussionmentioning
confidence: 99%
“…Five features distinguish these CHW: 1) they are selected based on being positive peer deviants (Bolles, Speraw, Berggren, & Lafontant, 2002); 2) CHW are trained to address multiple health challenges, not only one; 3) there are clear expectations for performance (e.g., a defined caseload of 40 families) and accountability structures for both interpersonal supervision and monitoring by paper documentation of visits or mobile phones; 4) CHWs are encouraged to leverage their relationship to motivate mothers to care well for their infants; and, 5) the CHW are paid a stipend and only employed half time (as this is the first job for almost all the CHW).…”
Section: Discussionmentioning
confidence: 99%